Saturday

April 19, 2014

April 19, 2014

Posted by **beth** on Wednesday, January 5, 2011 at 5:44pm.

- algebra -
**Ms. Sue**, Wednesday, January 5, 2011 at 5:47pm8x-(6x+7)=3 x

2x - 7 = 3x

2x - 3x = 7

x = -7

**Related Questions**

Business Calculus - The indefinite integral, or which call the "antiderivative...

algerbra 1 - 5x+8+3x-x+5=6x-3 do I start like this 5x+3x-x or 5x+3x+8+5=6x-3 I ...

algebra - what is a quartic function with only the two real zeros given x=5 and ...

algebra - collect like terms 8x^2+6x^4-2x^2-x^4-6x^2

algebra 1 - find the quotient 6x^4+6x^3+8x^2 --------------- 2x^2

Algebra - Factorise completely: 6x^2+10x-5= and 6x^2+8x-3=

Algebra - Factorise completely: 6x^2+10x-5= and 6x^2+8x-3=

Algebra - Find the product: -6x(-8x^2+x+5) A)-14x^3-5x^2-x B)48x^3+x+5 C)48x^3-...

math - 1)y=x²-3x+2 2)y=8x-16/x-3 A)Sketch both on axes B)Calculate coordinate of...

Algebra - Please check for me. 7p - 7/p divided by 10p-10/5p^2 = 7p^2 6x - 6/x...